The Last temptation of Christ - Kazantzakis, Nikos; Kazantzakis, Nikos, 1883-1957.; Scorsese, Martin; Schrader, Paul, 1946-; Dafoe, Willem; Keitel, Harvey; Hershey, Barbara, 1948-; De Fina, Barbara; Hershey, Barbara, 1948-; Stanton, Harry Dean, 1926-2017; Bowie, David; Universal Pictures (Firm); et al. (London : Simon and Schuster, 1960)
In this controversial movie Jesus, as both fully human and fully divine, is viewed in this film free of sin but subject to all temptations, including sexual ones
Music, Peter Gabriel ; editor, Thelma Schoonmaker ; director of photography, Michael Ballhaus
Screenplay, Paul Schrader ; music, Peter Gabriel ; editor, Thelma Schoonmaker
Willem Dafoe (Jesus), Harvey Keitel (Judas), Barbara Hershey (Mary Magdalene), Paul Greco, Steven Shill, Verna Bloom
Willem Dafoe (Jesus), Harvey Keitel (Judas), Barbara Hershey (Mary Magdalene), Harry Dean Stanton (Paul), David Bowie (Pontius Pilate)
Cast: Willem Dafoe (Jesus), Harvey Keitel (Judas), Barbara Hershey (Mary Magdalene), Harry Dean Stanton (Paul), David Bowie (Pontius Pilate)
Keywords: Jesus Christ -- Drama; Christ; Feature films; Video recordings; Drama